Anemia associated with chronic heart failure: current concepts - Shah R (Dove Medical Press, 2013)
Ravish Shah, Anil K AgarwalDivision of Nephrology, The Ohio State University, Columbus, Ohio, USAAbstract: Anemia is a frequent comorbidity of heart failure and is associated with poor outcomes. Anemia in heart failure is considered to develop due to a complex interaction of iron deficiency, kidney disease, and cytokine production, although micronutrient insufficiency and blood loss may contribute. Currently, treatment of anemia of heart failure lacks clear targets and specific therapy is not defined. Intravenous iron use has been shown to benefit anemic as well as nonanemic patients with heart failure. Treatment with erythropoietin-stimulating agents has been considered alone or in combination with iron, but robust evidence to dictate clear guidelines is not currently available. Available and emerging new agents in the treatment of anemia of heart failure will need to be tested in randomized, controlled studies.Keywords: anemia, heart failure, chronic kidney disease, elderly population